2, 2′‐Dipyridyl diselenide: A chemoselective tool for cysteine deprotection and disulfide bond formation. (19th December 2019) - Ste.Marie, Emma J.; Hondal, Robert J.
Abstract : There are many examples of bioactive, disulfide‐rich peptides and proteins whose biological activity relies on proper disulfide connectivity. Regioselective disulfide bond formation is a strategy for the synthesis of these bioactive peptides, but many of these methods suffer from a lack of orthogonality between pairs of protected cysteine (Cys) residues, efficiency, and high yields. Here, we show the utilization of 2, 2′‐dipyridyl diselenide (PySeSePy) as a chemical tool for the removal of Cys‐protecting groups and regioselective formation of disulfide bonds in peptides. We found that peptides containing either Cys(Mob) or Cys(Acm) groups treated with PySeSePy in trifluoroacetic acid (TFA) (with or without triisopropylsilane (TIS) were converted to Cys‐S–SePy adducts at 37 °C and various incubation times. This novel Cys‐S–SePy adduct is able to be chemoselectively reduced by five‐fold excess ascorbate at pH 4.5, a condition that should spare already installed peptide disulfide bonds from reduction. This chemoselective reduction by ascorbate will undoubtedly find utility in numerous biotechnological applications. We applied our new chemistry to the iodine‐free synthesis of the human intestinal hormone guanylin, which contains two disulfide bonds. While we originally envisioned using ascorbate to chemoselectively reduce one of the formed Cys‐S–SePy adducts to catalyze disulfide bond formation, we found that when pairs of Cys(Acm) residues were treated with PySeSePy in TFA, the second disulfide bond formed spontaneously. Spontaneous formation of the second disulfide is most likely driven by the formation of the thermodynamically favored diselenide (PySeSePy) from the two Cys‐S–SePy adducts. Thus, we have developed a one‐pot method for concomitant deprotection and disulfide bond formation of Cys(Acm) pairs in the presence of an existing disulfide bond. Abstract : 2, 2′‐Dipyridyl diselenide can deprotect Cys(Acm) and Cys(Mob) residues, converting them to a Cys‐S–SePy adduct, which can then be chemoselectively reduced by ascorbate without reducing an existing disulfide bond. The chemoselective reduction of the S–Se bond by ascorbate has many potential applications. We showed the use of this deprotection scheme to synthesize guanylin, a human hormone that contains two disulfide bonds.